'Applied science' in nineteenth-century Britain: public discourse and the creation of meaning, 1817-1876 - Bud, Robert (History and technology, 2014)
'Applied science' has long been a competitor with the concept of technology for the space between theory and praxis. This paper explores how the concept emerged in mid-nineteenth-century Britain through public sphere discussions in a cycle of rhetoric that linked the press, the development of new educational institutions and the interpretation of industrial change. The recounting and reprinting of heroic narratives of achievement served to cement alliances between 'practical men' and 'men of science' by proclaiming a respectable subject of common interest to which both could be associated. Narratives of applied science were drawn on in the process of institutional change. A key role was played by editors and business proprietors in local contexts; their interest in applied science stimulated the formation of new universities aimed at providing new forms of technical education. The use of the concept of 'applied science' to describe the space between science and practice challenged the traditional notion of 'rule of thumb' as a characterisation of shop work. With its connotations relating to both past and future, the term served to structure time as well as science.